Comparison of Whey Versus Almond Protein Powder on Nitrogen Balance in Female College Students; The California Almond Protein Powder Project (CAlmond-P3) - Adeline Maykish (MDPI AG, 2021)
Plant-based diets have become increasingly popular in the past decade, with approximately 11% of Americans self-identifying as vegan or vegetarian and many others trying to reduce meat consumption. Due to increasing interest, the plant-based food market has significantly expanded, with several innovative products serving as alternatives to animal-based products. One such example is almond protein powder, a new protein supplement created as an alternative to whey protein. Due to the novelty of almond protein products, little is known regarding how well the protein supplement supports nitrogen metabolism. The effects of both an almond-based protein beverage and a whey-based protein beverage on nitrogen balance are investigated in the work presented herein. Twenty female college students aged 20–25 years were randomly assigned to consume either an almond- or whey-based protein drink twice daily for one week; 24-h urine collection was performed at the baseline and endpoint of the 7-day treatment period and nitrogen balance was assessed. Body composition and hydration status were also assessed. Both protein sources (almond and whey) were able to notably improve nitrogen balance, thus indicating that almond protein powder may be a functional plant-based alternative to whey protein powder and may be of interest in future research regarding muscle mass and body composition improvement.